2003
DOI: 10.3168/jds.s0022-0302(03)73883-1
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Localization and Abundance of Laminin, Fibronectin, and Collagen IV Proteins in Prepubertal Heifers

Abstract: The objective was to determine localization and abundance of extracellular matrix proteins fibronectin, laminin, and collagen in mammary tissues from ovariectomized or intact prepubertal heifers. Mammary parenchyma and fat pad tissues were collected from 14 6-mo-old heifers: eight were ovariectomized between 1 to 3 mo of age, and six were used as intact controls. Distribution of total collagen was assessed by Sirius Red staining of tissue sections. Fibronectin, laminin, and type IV collagen were assessed by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This protein has been found to be expressed in BC [40, 41], and other cancers [37, 42, 43]. Moreover, it has been reported that FN could induce progression of various cancer cells [36, 37] and is strongly expressed in breast carcinoma, and its distribution is different from that of normal breast parenchyma [38, 39]. Although measurement of FN levels in other cancer groups is necessary, we have limitation in this study to collect patients' plasma with other cancers in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has been found to be expressed in BC [40, 41], and other cancers [37, 42, 43]. Moreover, it has been reported that FN could induce progression of various cancer cells [36, 37] and is strongly expressed in breast carcinoma, and its distribution is different from that of normal breast parenchyma [38, 39]. Although measurement of FN levels in other cancer groups is necessary, we have limitation in this study to collect patients' plasma with other cancers in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their observations, these authors suggested a role for the integrins in coordinating the cytoskeleton and regulating the induction of cellular differentiation by PRL. To regulate cellular proliferation and mammary growth, ECM influences the cellular response to steroid hormones (Wilde et al, 1984), and also appears to interact with local growth factor signaling pathways (Berry et al, 2003). In addition, remodeling of ECM and mammary involution is induced by decreased milking frequency and milk stasis in ruminants (Weng et al, 2008).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…In contrast to the prelevation of mammary tissue biopsies through invasive surgery (Knight et al, 1992;Farr et al, 1996) or at necropsy (Cifrian et al, 1994;Berry et al, 2003;Pfaffl et al, 2003), the endoscopic procedure yields much smaller amount of mammary tissue. The limited sample size did not, however, compromise the possible applications of the technique.…”
Section: Discussionmentioning
confidence: 99%